Prevalence of Hospital Functional Impairment in a Colombian Elderly Population at the San Ignacio University Hospital (2019)
Introduction: Functional decline following hospitalization (FDH) is defined as the loss of the functional capacity to perform at least one basic activity of daily life (BADL) when being discharged from hospital; a situation compared to functional capacity performed in the last couple of weeks, prior the acute disease. This impairment is precipitated in the elderly by factors such as aging, architectural conditions, malnutrition, hospital routines and physical restraints. The objective of this study is determining the prevalence of functional impairment in adults over 65 years of age hospitalized in the San Ignacio University Hospital (SIUH) and its associated factors. Materials and Methods: A descriptive cross-sectional study of a hospital cohort was carried out from December 1st 2015 to December 31st 2017. Univariate and multivariate analyses were performed to identify associated variables. Results: 1055 people were included,with fdh prevalence of 41.14 %. The three main factors associated with the development of fdh in the elderly population that consulted the siuh were time of hospital stay [or 1.88, CI95% (1.41-2.49), p = <0.0001], malnutrition [or 1.59, CI95 % (1.16-2.19), p = 0.004] and delirium [or 2.38, CI95 % (1.83-3.10), p = <0.001]. Conclusion: FDH is a highly prevalent condition in the geriatric population hospitalized in the San Ignacio University Hospital, where length of stay, malnutrition and delirium are the factors associated with its disease onset.